2022
DOI: 10.1002/advs.202104836
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis Imbalance of YY2 and YY1 Promotes Tumor Growth by Manipulating Ferroptosis

Abstract: Ferroptosis is a type of programmed cell death caused by disruption of redox homeostasis and is closely linked to amino acid metabolism. Yin Yang 2 (YY2) and its homolog Yin Yang 1 (YY1) are highly homologous, especially in their zinc-finger domains. Furthermore, they share a consensus DNA binding motif. Increasing evidences have demonstrated the tumor suppressive effect of YY2, in contrast with the oncogenic YY1; however, little is known about the biological and pathological functions of YY2. Here, it is dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…Ferroptosis modulates the pathogenesis and the progression of HCC. For example, metallothionein‐1G, 15 the p62/NRF2 pathway, 26 and the S47 variant of the TP53 gene 37 all protect against ferroptosis and hepatocarcinogenesis 38–40 . However, the regulation of SLC7A11 and cell ferroptosis by lncRNA remains largely uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis modulates the pathogenesis and the progression of HCC. For example, metallothionein‐1G, 15 the p62/NRF2 pathway, 26 and the S47 variant of the TP53 gene 37 all protect against ferroptosis and hepatocarcinogenesis 38–40 . However, the regulation of SLC7A11 and cell ferroptosis by lncRNA remains largely uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GPX4 is considered a crucial molecule in the regulation of ferroptosis [ 24 ]. The basis of ferroptosis is the presence of free iron in the cells.…”
Section: Ferroptosismentioning
confidence: 99%
“…Furthermore, GPX4 is considered a crucial molecule in the regulation of ferroptosis [24]. The basis of ferroptosis is RCD: regulated cell death; PTGS2: prostaglandin endoperoxide synthase 2; FSP1: fibroblast-specific protein 1; NRF2: nuclear factor erythroid 2-related factor 2; DFO: desferrioxamine.…”
Section: Underlying Mechanisms Of Ferroptosismentioning
confidence: 99%
“…Yin Yang 2 (YY2) protein manipulated cellular redox homeostasis, which induced tumor cell ferroptosis and suppressed tumorigenesis. Mechanistically, YY2 competed against its homolog YY1 to bind SLC7A11 promoter, which blocked transcription of SLC7A11 and associated GSH biosynthesis (182). Mutation of YY2 zincfinger domains disturbed the interaction between YY2 and SLC7A11, and abrogated ferroptosis (182).…”
Section: Zn and Zn Binding Protein Promote Regulated Necrosismentioning
confidence: 99%
“…Mechanistically, YY2 competed against its homolog YY1 to bind SLC7A11 promoter, which blocked transcription of SLC7A11 and associated GSH biosynthesis (182). Mutation of YY2 zincfinger domains disturbed the interaction between YY2 and SLC7A11, and abrogated ferroptosis (182). A20 was identified that directly interacted with ACSL4, whose upregulation promoted erastin-induced ferroptosis in endothelial cells (183).…”
Section: Zn and Zn Binding Protein Promote Regulated Necrosismentioning
confidence: 99%